2023
DOI: 10.1136/jitc-2022-005968
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumor-associated macrophages for successful immunotherapy of ovarian carcinoma

Abstract: Epithelial ovarian cancer (EOC) is among the top five causes of cancer-related death in women, largely reflecting early, prediagnosis dissemination of malignant cells to the peritoneum. Despite improvements in medical therapies, particularly with the implementation of novel drugs targeting homologous recombination deficiency, the survival rates of patients with EOC remain low. Unlike other neoplasms, EOC remains relatively insensitive to immune checkpoint inhibitors, which is correlated with a tumor microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 194 publications
(137 reference statements)
2
20
0
Order By: Relevance
“…VEGFA and VEGFB expressed in tumor cells potentially interact with NRP1 , and FLT1 is particularly expressed in endothelial cells. Blocking macrophage colony-stimulating factor CSF1 and its receptor CSF1R axis and several drugs that target these factors have been under investigation [71].…”
Section: Resultsmentioning
confidence: 99%
“…VEGFA and VEGFB expressed in tumor cells potentially interact with NRP1 , and FLT1 is particularly expressed in endothelial cells. Blocking macrophage colony-stimulating factor CSF1 and its receptor CSF1R axis and several drugs that target these factors have been under investigation [71].…”
Section: Resultsmentioning
confidence: 99%
“…M2 macrophages commonly predominate in the ovarian cancer environment [ 22 , 23 ]. Thus, it may be crucial to reprogram the TAMs in TME to improve the strong immunosuppression and increase therapeutic effectiveness of ovarian cancer, with the aim of providing a new insight for immunotherapy in ovarian cancer [ 24 , 25 ]. Interestingly, based on the assessments of the TIMER and EPIC databases, we found that the tumor environment comprised CAFs (cancer-associated fibroblasts), CD4+/CD8+ T cells, and macrophages, revealing that the immune microenvironment of ovarian cancer presents a dichotomy between immune activation and suppression.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 CCL2/CCR2 or CSF1/CSF1R blockades deplete TAMs and have been tested in clinical trials. [48][49][50] In addition, MDSCs are depleted by chemotherapies, such as anti-VEGF antibody, 5-fluorouracil, gemcitabine, or the CXCR2 blockade. 40,51,52 Immunotherapies should also aim to increase the number of neoantigens to allow T cells to target tumor cells.…”
Section: Future Perspectives In Immunotherapies For Ovarian Cancermentioning
confidence: 99%
“…Anti‐CLTA‐4, anti‐CD25, or anti‐CCR4 antibodies are good treatment options for Treg depletion 46,47 . CCL2/CCR2 or CSF1/CSF1R blockades deplete TAMs and have been tested in clinical trials 48–50 . In addition, MDSCs are depleted by chemotherapies, such as anti‐VEGF antibody, 5‐fluorouracil, gemcitabine, or the CXCR2 blockade 40,51,52 …”
Section: Future Perspectives In Immunotherapies For Ovarian Cancermentioning
confidence: 99%